THEMATIC LEARNING MANAGEMENT DURING THE NEW NORMAL ERA AT STATE ISLAMIC ELEMENTARY SCHOOL - Sri Enggar Kencana Dewi; Ratih Purnama Pertiwi; Diyah Pravitasari (JIP Jurnal Ilmiah PGMI, 2021)
This research was motivated by the importance of understanding the thematic learning management in the New Normal Era. This study aimed to determine planning, implementation and assessment of the thematic learning in the new normal era in State Islamic Elementary School (MIN) at East OKU. The researcher used a qualitative research that was carried out at MIN at East OKU. The data collection techniques which were used are observation, interviews and documentation. The used validity test of the data was triangulation technique. The results of this study indicated that the planning process continues to make learning media (the details on effective week, the annual program, the semester program, the syllabus, the lesson plans, the analysis of learning outcomes, as well as remedial and enrichment programs) adapted to offline or online learning patterns. The implementation of learning in the new normal era continues to carry out learning as usual in line with the lesson plans which was made and learning media that are in line with the material presented. The implementation pattern of learning was adjusted to the predetermined time, namely shifts (odd-even) for low and high grades. One class was limited to a maximum of 20 students and the study hours are also reduced, usually learning is until 12:45 while in the new normal era students only arrive at 09.00 or 10.00. Then in the assessment process carried out at MIN, namely daily tests (after completing 1 sub-theme or 2 sub-themes), in addition to UTS (mid-semester assessment), and PAS (final semester assessment) which has been scheduled on the educational calendar. In this school, the assessment applied also carries out a character assessment.